Self-regulation and eating behaviour in Portuguese children and adolescents : concept mapping methodology - Gaspar, Tânia, 1977- (2012)
The present study analyses self-regulatory perspectives related to healthy eating behaviour. The research aims to examine the ideas that children and adolescents have about their own self-regulation and what aspects are important in order to resist food temptations. This study it is included in a major European research project named TEMPEST http-//tempestproject.eu/. The qualitative method concept mapping was used. To the sample composed by 100 individuals of both genders, aged between 12 and 17 years old, were applied the three stages of concept mapping process. The students belonged to different schools of districts of Leiria and Santarem, in Portugal. Two classes were selected with students between 12 and 14 years old, one with a low socio-economic status and other with a high socio-economic status. At the same time, two other classes were selected with students with ages between 14 and 17 years and with the same socio-economic status features. Socio-economic status was defined according to the type of school and its location. (Tânia Gaspar, Margarida Gaspar de Matos)